Comparison of Informal Care Time and Costs in Different Age-Related Dementias: A Review. (31st October 2012) - Costa, Nadège; Ferlicoq, Laura; Derumeaux-Burel, Hélène; Rapp, Thomas; Garnault, Valérie; Gillette-Guyonnet, Sophie; Andrieu, Sandrine; Vellas, Bruno; Lamure, Michel; Grand, Alain; Molinier, Laurent
Abstract : Objectives . Age-related dementia is a progressive degenerative brain syndrome whose prevalence increases with age. Dementias cause a substantial burden on society and on families who provide informal care. This study aims to review the relevant papers to compare informal care time and costs in different dementias. Methods . A bibliographic search was performed on an international medical literature database (MEDLINE). All studies which assessed the social economic burden of different dementias were selected. Informal care time and costs were analyzed in three care settings by disease stages. Results . 21 studies met our criteria. Mean informal care time was 55.73 h per week for Alzheimer disease and 15.8 h per week for Parkinson disease (P = 0.0076 ), and the associated mean annual informal costs were $17, 492 versus $3, 284, respectively (P = 0.0393 ). Conclusion . There is a lack of data about informal care time and costs among other dementias than AD or PD. Globally, AD is the most costly in terms of informal care costs than PD, $17, 492 versus $3, 284, respectively.